Correlations between pediatric obstructive sleep apnea and longitudinal growth. (March 2018) - Park, Do-Yang; Choi, Ji Ho; Kang, So Young; Han, Jinjoo; Park, Hun Yi; Hwang, Jin Soon; Cho, Jae Ho; Cho, Min Hyuk; Kim, Hyun Jun
Abstract: Objectives: Pediatric obstructive sleep apnea has a relatively high prevalence and has various negative health and behavioral consequences. Among the various complications of pediatric obstructive sleep apnea, growth disturbance is still controversial. Method: 745 pediatric subjects with obstructive sleep apnea diagnosed by in-lab polysomnography were enrolled, after excluding ineligible subjects with abnormal growth related factors. Height, weight, and BMI of enrolled patients were measured and statistically converted to z-scores, and the converted data were analyzed statistically with the polysomnographic results. Multiple linear regression were used to analyze the relationships between age, gender, z-score for weight, polysomnography results, and z-score for height. Results: Patients with higher respiratory related index or lower mean/lowest oxygen saturation of PSG showed smaller z-score for height. Mean apnea hypopnea index and standard deviation of enrolled patients was 7.46 ± 12.92, with moderate severity. And mean z-score for height and standard deviation was 0.21 ± 1.15. Apnea hypopnea index, respiratory disturbance index, obstructive apnea index, and hypopnea index, respiratory related results of polysomnography, were statistically negative correlated with a z-score for height. And mean oxygen saturation and lowest oxygen saturation, oxygen saturation results of polysomnography, were statistically positive correlated with a z-score for height. Conclusions: Respiratory related results and oxygen saturation results of polysomnography show negative and positive correlation with z-score for height. Therefore, pediatric obstructive sleep apnea have a negative effect on longitudinal growth.